2017
DOI: 10.1016/j.neuroimage.2017.08.049
|View full text |Cite
|
Sign up to set email alerts
|

A brain-based account of “basic-level” concepts

Abstract: This study provides a brain-based account of how object concepts at an intermediate (basic) level of specificity are represented, offering an enriched view of what it means for a concept to be a basic-level concept, a research topic pioneered by Rosch and others (Rosch et al., 1976). Applying machine learning techniques to fMRI data, it was possible to determine the semantic content encoded in the neural representations of object concepts at basic and subordinate levels of abstraction. The representation of ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 60 publications
(93 reference statements)
0
10
0
Order By: Relevance
“…The distinct activation patterns between groups could be reflected in the multi-voxel spatial pattern and/or a systemic difference across voxels (Jimura & Poldrack, 2012;Kragel, Carter, & Huettel, 2012). Therefore, follow-up analyses were conducted in regions with significant MVPA results to evaluate whether the potential group differences in activation levels contributed to the distinct activation patterns observed between FHD−Typical and FHD+Typical children (Bauer & Just, 2017;Coutanche, 2013). Since the MVPA considers information across multiple voxels (i.e., activation pattern) as a whole, the subsequent analyses of the group differences in individual voxels were conducted within the context of their contributions to the whole classification model (see a similar analysis in Evans et al, 2014).…”
Section: In-scanner Performancementioning
confidence: 99%
“…The distinct activation patterns between groups could be reflected in the multi-voxel spatial pattern and/or a systemic difference across voxels (Jimura & Poldrack, 2012;Kragel, Carter, & Huettel, 2012). Therefore, follow-up analyses were conducted in regions with significant MVPA results to evaluate whether the potential group differences in activation levels contributed to the distinct activation patterns observed between FHD−Typical and FHD+Typical children (Bauer & Just, 2017;Coutanche, 2013). Since the MVPA considers information across multiple voxels (i.e., activation pattern) as a whole, the subsequent analyses of the group differences in individual voxels were conducted within the context of their contributions to the whole classification model (see a similar analysis in Evans et al, 2014).…”
Section: In-scanner Performancementioning
confidence: 99%
“…At higher levels, more areas are included in the categorization which was introduced by Bamer and Just in 2017 [31]. They examined two levels of basic and subordinate and expressed the basic level advantages.…”
Section: Discussionmentioning
confidence: 99%
“…Mean PSCs were normalized across voxels for each trial (MPSC). Previous studies have reported that the mean activation across these four images (as opposed to a GLM measure) yields a high classification accuracy obtained by a classifier that relates the activation pattern to the concept (Bauer & Just, 2017 ; Just et al, 2010 ; Mason & Just, 2016 ).…”
Section: Methodsmentioning
confidence: 99%